"Being connected" The experience of African American women with breast cancer: A community-based participatory research project: Part I. Issue 4 (4th July 2018) - Knobf, M. Tish; Erdos, Diane
ABSTRACT: The objective was to understand the breast cancer experience of African American (AA) women using a community-based participatory research framework. Qualitative data were collected from five focus groups with 29 participants in four urban cities. " Being Connected" was the major theme that explained the importance of people in their lives as they coped with the diagnosis, treatment, and life after therapy. Faith, talking, information, support, and living with changes were important factors in the process. The breast cancer experience was situated with the AA culture and community and unique aspects were identified for clinical practice in the care of these women.